Semisynthesis and anti-cancer properties of novel honokiol derivatives in human nasopharyngeal carcinoma CNE-2Z cells - Bo-Han Li; Hui Ma; Jing Zhu; Jie Chen; Yi-Qun Dai; Xiao-Jing Zhang; Hong-Mei Li; Cheng-Zhu Wu (Taylor & Francis Group, 2023)
In this study, 21 new honokiol derivatives were synthesised, and their anti-cancer properties were investigated. Among these, compound 1g exhibited the most potent cytotoxic activity against human nasopharyngeal carcinoma CNE-2Z cells, human gastric cancer SGC7901 cells, human breast cancer MCF-7 cells, and mouse leydig testicular cancer I-10 lines with IC50 values of 6.04, 7.17, 6.83, and 5.30 μM, respectively. Compared to the parental compound, 1g displayed up to 5.18-fold enhancement of the cytotoxic effect on CNE-2Z cells. We further demonstrated that 1g inhibited cell growth, suppressed migration and invasion, and induced apoptosis of CNE-2Z cells by down-regulating HIF-1α, MMP-2, MMP-9, Bcl-2, Akt and up-regulating Bax protein levels. Transfection of CNE-2Z cells with HIF-1α siRNA reduced cell migration and invasion. In addition, in vivo experiments confirmed that 1g inhibited tumour growth in CNE-2Z cell-xenografted nude mice with low toxicity. Thus, our data suggested that 1g was a potent and safe lead compound for nasopharyngeal carcinoma therapy.